2014
DOI: 10.1002/bjs.9385
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the effect of perioperative synbiotics versus no synbiotics on bacterial translocation after oesophagectomy

Abstract: ID 000003262 (University Hospital Medical Information Network, http://www.umin.ac.jp).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 23 publications
4
57
2
1
Order By: Relevance
“…This takes the form of defense against bacterial translocation and infectious complications in seriously ill patients, including perioperative patients with bile duct cancer (21,39), esophageal cancer (51,52), hepatic cirrhosis (53), and colorectal cancer (54), patients undergoing cancer chemotherapy (55), systemic inflammatory response syndrome (SIRS) patients (40), and patients on long-term mechanical ventilation (56). Moreover, research has suggested that improvement of dysbiosis and activity to improve the intestinal environment (pH and organic acid [acetic acid] level) are important in the mechanism for this protective effect against infections.…”
Section: Figmentioning
confidence: 99%
“…This takes the form of defense against bacterial translocation and infectious complications in seriously ill patients, including perioperative patients with bile duct cancer (21,39), esophageal cancer (51,52), hepatic cirrhosis (53), and colorectal cancer (54), patients undergoing cancer chemotherapy (55), systemic inflammatory response syndrome (SIRS) patients (40), and patients on long-term mechanical ventilation (56). Moreover, research has suggested that improvement of dysbiosis and activity to improve the intestinal environment (pH and organic acid [acetic acid] level) are important in the mechanism for this protective effect against infections.…”
Section: Figmentioning
confidence: 99%
“…Administration of synbiotics prevented postoperative deterioration of the intestinal microfloral environment and suppressed excessive inflammatory response, possibly by exerting immunomodulatory effects and by inhibiting bacterial translocation [88,89]. Additionally, synbiotics led to decreased incidence of severe diarrhea and lower interruption or reduction of enteral nutrition.…”
Section: Esophageal Abnormalitiesmentioning
confidence: 99%
“…This high analytical sensitivity enables more accurate and reliable detection (compared with conventional culture methods) of microorganisms that have migrated into the bloodstream, a condition known as bacteremia. Using this method, bacteremia was detected far earlier, and in some cases unexpectedly, in individuals, including adults subjected to invasive abdominal surgery [2] and pediatric surgical patients [5]. The analytical method was found to be useful for the detection of bacteremia in pediatric patients with febrile neutropenia (mucositis) [6], type 2 diabetes [7], and ischemic stroke [8].…”
Section: A Cutting-edge Analytical Methods For Detection Of Bacteria Imentioning
confidence: 99%
“…This study group also demonstrated these findings in the context of dysbiosis-related deteriorations of the gut environment [9]. One of the excellent papers of Prof. Y. Yokoyama’s group [5] is summarized below.…”
Section: Bacteremia In Highly Invasive Abdominal Surgery and Its Prevmentioning
confidence: 99%